L’espace politique des médicaments - Alain Vaguet (L'Espace Politique)
The main contemporary debates around health products may concern doubts about the therapeutic potential of molecules of allopathic medicine. But at the same time, issues concerning access to essential medicines are still valid in the least developed countries and even in the "Emerging". For developed countries themselves, increasing costs of new specialties is also becoming a concern to maintain balanced health budgets and equal access. In total, as has been said for the great pandemics, health products are, they too, good observatories of globalization. But if we remember that, apart from a few scattered studies, no drug atlas has been published, it measures the state of incompleteness of this issue.In the context of this article, inaccessibility to medicines is considered a significant health risk. An initial summary review of the main issues is presented at various levels: local, national, international or global; as well as the alternatives that are being considered.To present this theme, a documentary monitoring was conducted for several years, both in academic publications, but also in the register of critical forums. A methodological shift will explain a specific focus on the positions of India and its militants; in fact, this country now has a central but ambiguous position.Drug prices are good indicators, they reflect the interests, often conflicting, of the various actors involved: States, pharmaceutical companies, international organizations, charitable foundations but also global citizens and activists. The scope of these decisions, very serious in humanitarian terms and completely beyond territorial boundaries, therefore leads to question the ethics of this trade and international relations incurred.